Homeworking in Slovenia - Širok, Klemen (IB revija (Ljubljana), 2019)
The paper addresses the incidence, specifics and nature of homeworking in Slovenia. There is lack of empirical research on homeworking, both in Slovenia and internationally, which might be related to the lack of reliable records of homeworking. In this paper we therefore analyse homeworking by combining different survey datasets, including Labour Force Survey, the Community Survey on ICT Usage in Households and by Individuals and the European Working Conditions Survey. We find that the incidence of homeworking in Slovenia is close or little above the EU average, but it is not being used %in accordance with the homeworking purpose%, i. e. higher flexibility and a better work-life relationship. Although the incidence of homeworking is higher among higher educated, workers with higher incomes, mothers, workers with children and in industries such as information and communication services, financial and insurance services and professional services (i. e., among workers for whom the homeworking might be more attractive), most of homeworkers engage in this type of work either to finish the work that was not done during the regular worktime or of own interest.
Keywords: delo; delo na domu; fleksibilnost; flexibility; homeworking; labour market; Slovenia; Slovenija; trg dela; work